Boosting Reading Comprehension Performance: The Impact of Metacognitive Reading Strategies on Grade 11 Students - Jugas, Ralph Jade M. (International Journal of Contemporary Sciences (IJCS), 2024)
This study investigates the impact of metacognitive reading strategies on enhancing the reading comprehension of Grade 11 HUMSS students in the Reading and Writing Skills subject at i-Link College of Science and Technology in SY 2023-2024. Using an explanatory sequential research design over four weeks, strategies such as SQ3R, inferring and predicting, visualizing, and summarizing were applied. Pretest and posttest scores were analyzed, revealing significant improvement (p=0.00) with a large effect size (d=0.82). Focus Group Discussion highlighted seven themes, including confidence, engagement, and self-efficacy. A joint display confirmed alignment between quantitative and qualitative findings, indicating that metacognitive strategies effectively boost reading comprehension and academic performance, offering a promising approach for pedagogical enhancement.